Electrodeposited 3D hierarchical NiFe microflowers assembled from nanosheets robust for the selective electrooxidation of furfuryl alcohol - Biying Liu; Man Zhang; Yaoyu Liu; Yuchen Wang; Kai Yan (Green Energy & Environment, 2023)
A robust and green strategy for the selective upgrading of biomass-derived platform chemicals towards highly valuable products is important for the sustainable development. Herein, the efficient electrocatalytic oxidation of biomass-derived furfuryl alcohol (FFA) into furoic acid (FurAc) catalyzed by the electrodeposited non-precious NiFe microflowers was successfully reached under the low temperature and ambient pressure. The 3D hierarchical NiFe microflowers assembled from ultrathin nanosheets were controllably synthesized by the electrodeposition method and uniformly grown on carbon fiber paper (CFP). Electrochemical analysis confirmed that NiFe nanosheets more preferred in the selective oxidation of FFA (FFAOR) than oxygen evolution reaction (OER). The linear sweep voltammetry (LSV) in FFAOR displayed a clear decrease towards lower potential, resulting in 30 mV reduction of overpotential at 20 mA cm−2 compared with that of OER. The optimal catalyst Ni1Fe2 nanosheets exhibited the highest selectivity of FurAc (94.0%) and 81.4% conversion of FFA within 3 h. Besides, the influence of various reaction parameters on FFAOR was then explored in details. After that, the reaction pathway was investigated and rationally proposed. The outstanding performance for FFAOR can be ascribed to the unique structure of 3D flower-like NiFe nanosheets and oxygen vacancies, resulting in large exposure of active sites, faster electron transfer and enhanced adsorption of reactants. Our findings highlight a facile and convenient mean with a promising green future, which is promising for processing of various biomass-derived platform chemicals into value-added products.